Evaluation of Architectural Publicness Design Elements on Seremban State Mosque of Negeri Sembilan - Nangkula Utaberta; mohd tajuddin mohd rasdi; Teoh Chee Keong; Lee Yun Sheng (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2022)
This research paper aims to examine the architectural design and the publicness of a state mosque in Malaysia while taking into consideration the social inclusiveness and national identity among religious buildings within the compound and beyond the framework of religion. The research objective is to evaluate the architectural design elements in a mosque on publicness. The methodology used in this research is by reviewing literature and evaluating the Negeri Sembilan State Mosque; Seremban Mosque, as a case study of its social publicness. The finding from the research concludes that the state mosque can do more to achieve inclusivity and friendliness through architectural design elements such as perception, permeability, and territoriality of the building in relation to its context and religious adherents, as well as the larger Malaysian population. Furthermore, the significance of the finding identified that religion and religious buildings play a crucial role in sustaining unity and harmony among all ethnicity in a community with such a diverse society in order to promote further the manifestation of social inclusiveness and national unity among religious buildings and diminish the conflict in race and religion.